N-methyl costaricine and costaricine, two potent butyrylcholinesterase inhibitors from alseodaphne pendulifolia gamb - Mohd Azlan Nafiah (Tanjung Malim, 2023)
N-methyl costaricine and costaricine, two potent butyrylcholinesterase inhibitors from alseodaphne pendulifolia gamb by Mohd Azlan Nafiah